Monocular depth estimation based on deep learning for intraoperative guidance using surface-enhanced Raman scattering imaging - Aniwat Juhong; Bo Li; Yifan Liu; Cheng‐You Yao; Chia‐Wei Yang; Aman Ullah; Kunli Liu; Ryan P. Lewandowski; Jack R. Harkema; Dalen Agnew; Yu L. Lei; Gary D. Luker; et al. (Photonics Research, 2024)
Imaging of surface-enhanced Raman scattering (SERS) nanoparticles (NPs) has been intensively studied for cancer detection due to its high sensitivity, unconstrained low signal-to-noise ratios, and multiplexing detection capability. Furthermore, conjugating SERS NPs with various biomarkers is straightforward, resulting in numerous successful studies on cancer detection and diagnosis. However, Raman spectroscopy only provides spectral data from an imaging area without co-registered anatomic context. This is not practical and suitable for clinical applications. Here, we propose a custom-made Raman spectrometer with computer-vision-based positional tracking and monocular depth estimation using deep learning (DL) for the visualization of 2D and 3D SERS NPs imaging, respectively. In addition, the SERS NPs used in this study (hyaluronic acid-conjugated SERS NPs) showed clear tumor targeting capabilities (target CD44 typically overexpressed in tumors) by an ex vivo experiment and immunohistochemistry. The combination of Raman spectroscopy, image processing, and SERS molecular imaging, therefore, offers a robust and feasible potential for clinical applications.
Keywords: Spectroscopy Techniques in Biomedical and Chemical Research; Photoacoustic and Ultrasonic Imaging; Image Processing Techniques and Applications